Child Neurology: Functional Reorganization Mediating Supplementary Motor Area Syndrome Recovery in Agenesis of the Corpus Callosum. (26th July 2022) - Obaid, Sami; Qureshi, Hanya M.; Aljishi, Ayman; Shaikh, Neelam; Kundishora, Adam J.; Bronen, Richard A.; DiLuna, Michael; Damisah, Eyiyemisi C.
Abstract : Supplementary motor area (SMA) syndrome is a typically transient condition resulting from damage to the medial premotor cortex. The exact mechanism of recovery remains unknown but is traditionally described as a process involving functional compensation by the contralateral SMA through corpus callosal fibers. The purpose of this case study is to highlight a distinct extracallosal mechanism of functional recovery from an SMA syndrome in a patient with agenesis of the corpus callosum (ACC). We present the clinical presentation and perioperative functional neuroimaging features of a 16-year-old patient with complete ACC who exhibited recovery from an SMA syndrome resulting from surgical resection of a right-sided low-grade glioma. Preoperative fMRI revealed anatomically concordant activation areas during finger and toe tapping tasks bilaterally. Three months after surgery, the patient had fully recovered, and a repeat fMRI revealed shift of the majority of the left toe tapping area from the expected contralateral hemisphere to the ipsilateral left paracentral lobule and SMA. The fMRI signal remodeling observed in this acallosal patient suggests that within-hemisphere plasticity of the healthy hemisphere may constitute an alternative critical process in SMA syndrome resolution and challenges the traditional view that transcallosal fibers are necessary for functional recovery.